2022
DOI: 10.30773/pi.2022.0063
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Checklist for Predicting Suicidality Based on Risk and Protective Factors: The Gwangju Checklist for Evaluation of Suicidality

Abstract: Objective The aim of the study was to develop a checklist for mental health clinicians to predict and manage suicidality.Methods A literature review of the risk and protective factors for suicide was conducted to develop a checklist for evaluating suicidality.Results The fixed risk factors included sex (male), age (older individuals), history of childhood adversity, and a family history of suicide. Changeable risk factors included marital status (single), economic status (poverty), physical illness, history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 115 publications
1
4
0
Order By: Relevance
“…As in previous studies of patients with schizophrenia and the general population, the individuals in this study who had experienced SI showed significantly higher levels of depression and hopelessness (11,(73)(74)(75)(76). A higher general psychopathology PANSS score in patients with SI might be associated with depressive symptoms.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…As in previous studies of patients with schizophrenia and the general population, the individuals in this study who had experienced SI showed significantly higher levels of depression and hopelessness (11,(73)(74)(75)(76). A higher general psychopathology PANSS score in patients with SI might be associated with depressive symptoms.…”
Section: Discussionsupporting
confidence: 75%
“…Hopelessness is a major psychological risk factor and a clinical endophenotype for suicidality in the general population. Hopelessness plays a role in the development of suicidal thoughts and behaviors, and it also mediates the relationship between SI and suicidality ( 75 ). Demoralization, which is associated with hopelessness ( 79 ), is important in the context of the current study, which explored the link between cognitive function and SI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28] Being male is a high-risk factor for suicidal events. [29] The absence of gender-specific differences in the prevalence of NSSI might be explained by the similarity of negative life events encountered on campus, such as unsatisfactory academic performance, disappointment in love affairs, and finding the postgraduate entrance exam to be stressful. [30]…”
Section: Discussionmentioning
confidence: 99%
“…[28] Being male is a high-risk factor for suicidal events. [29] The absence of gender-specific differences in the prevalence of NSSI might be explained by the similarity of negative life events encountered on campus, such as unsatisfactory academic performance, disappointment in love affairs, and finding the postgraduate entrance exam to be stressful. [30] After controlling for the variables of school type and family structure, we found that individuals who were the only child in their family were much more likely to commit NSSI than those who were not.…”
Section: Discussionmentioning
confidence: 99%